IMPROVEMENT OF LASER TECHNOLOGY IN TREATMENT OF LATE ANASTOMOSITIS IN SURGERY OF GASTRIC AND DUDENAL ULCER (Experimental Research) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The authors analyze that for the treatment of late anastomosis after surgical interventions on the stomach and duodenum, it is recommended to include the laser action of the anastomosis zone with two types of low-energy lasers in the complex program.